The Effect Of Smart Phone Use Intensity On Academic Procrastination And Learning Motivation Of Students At Muhammadiyah University Of North Sumatera - Zulkarnain, Rif'at; Utami, Ratih Yulistika (Buletin Farmatera, 2027)
Abstract: Indonesia is a country with more than 190 million smartphone users. This makes Indonesia the fourth largest smartphone user in the world after China, India, and the United States. Students tend to use smartphones with high intensity. High smartphone use can lead to smartphone addiction. Objective: to analyze the effect of smartphone usage intensity on academic procrastination behavior and learning motivation in students at the University of Muhammadiyah North Sumatra. Method: This research is an analytical study using a cross-sectional method, with a sample of 63 people divided into 7 people each from 9 faculties at the University of Muhammadiyah North Sumatra. The sampling technique uses the Probability Sampling procedure, namely Consecutive Sampling. All samples filled out three questionnaires to measure the intensity of smartphone use, learning motivation, and academic procrastination. The data obtained will be analyzed using univariate and bivariate analysis techniques, then to test the hypothesis using the Spearman test to assess whether there is an influence between the independent and dependent variables. Results: The Spearman correlation test showed that smartphone usage intensity influenced academic procrastination among students at the University of Muhammadiyah North Sumatra, with a correlation coefficient of 0.790 (p-value of 0.001). The correlation coefficient of smartphone usage on learning motivation among students at the University of Muhammadiyah North Sumatra was -0.531 (p-value of 0.001), indicating a strong and negative relationship between the two variables. Conclusion: High smartphone usage intensity will increase academic procrastination, while high smartphone usage intensity will decrease student learning motivation.